Effects of different compression ratios and spark timings on performance and emissions of a two-wheeler with 30% ethanol-gasoline blend (E30). (1st October 2020) - Sakthivel, P.; Subramanian, K.A.; Mathai, Reji
Highlights: Effects of compression ratio and spark timing on performance and emissions were studied. Higher compression ratio increased vehicle power by 4.5% and decreased SFC by 8.9% This combined with optimal spark advance increased vehicle power by 8.0% Peak combustion pressure and heat release rate increased significantly. CO and HC emissions decreased with increase in NOx emissions. Abstract: 30% ethanol blended gasoline (E30) offers significant fuel quality advantages over normal gasoline. As the research octane number of E30 fuel is 100, the compression ratio of the engine was increased for improvement of fuel economy of vehicle. Experimental investigation was carried out on the effect of various compression ratios and spark timings on a two-wheeler with E30 fuel. The experiments were undertaken at different compression ratios (9.4:1, 10.9:1 and 11.5:1) and spark timings under wide-open throttle condition. The combustion, performance and emission characteristics were analyzed at different vehicle speeds. The test results showed that higher compression ratios increased vehicle power and decreased the specific fuel consumption. The maximum in-cylinder pressure increased with higher heat release rate and lower combustion duration. At high compression ratio, the hydrocarbon and carbon monoxide emissions decreased however, oxides of nitrogen emission increased. The spark timing advancement of 4°CA compared to the base timing was found optimal. This study highlights the importance of engine modification for efficient use of high-octane fuels.